Digital baseband processing for software radio modulator - 256142 Hazly Amir Abdul Hamid; Norsheila Fisal; Norazan Mohd. Kassim; Malaysian Science and Technology Congress (2000 : Genting Highlands, Pahang) (Skudai : Universiti Teknologi Malaysia, 2000)
16